2012
DOI: 10.6000/1927-5129.2012.08.02.25
|View full text |Cite
|
Sign up to set email alerts
|

The Palliative Effect of Bio-Organic Fertilizer on Lead Pollution in Lycopersicum esculentum Plants

Abstract: Lead is one of the hazardous heavy metal pollutants of the environment that originates from various sources. Soil contamination by lead reduces the quality of both soil and cultivated plants which often limits the production of some food products and animal feed. Thus, this study was undertaken to evaluate the effect of a bio-organic fertilizer, namely Acadian, a red algal extract, at recommended dose (RD) in alleviating the deteriorative effect of Pb at 0, 50, 100, 200 and 400 mg/l on tomato (Lycopersicum esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Several comparable studies confirmed the current data. For instance, Schuphan (2005), Noori et al (2010), Sivakumar and Ponnusami (2011) and Abdalla and El-Khoshiban, (2012) realized the increased uptake and accumulations of some nutritive elements as N, K, Ca, Mg, P as well as Fe in roots and shoots of several plants under investigation as a consequence of organic fertilization from different sources (plant and animal source) including Moringa leaf extract. Sivakumar and Ponnusami (2011) indicated that organic manures are fairly good source of nutrients which boosted plants to uptake progressively beneficial elements, to increase the leaf nutrient status and eventually attain optimum growth and productivity.…”
Section: Inorganic Nutrient Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several comparable studies confirmed the current data. For instance, Schuphan (2005), Noori et al (2010), Sivakumar and Ponnusami (2011) and Abdalla and El-Khoshiban, (2012) realized the increased uptake and accumulations of some nutritive elements as N, K, Ca, Mg, P as well as Fe in roots and shoots of several plants under investigation as a consequence of organic fertilization from different sources (plant and animal source) including Moringa leaf extract. Sivakumar and Ponnusami (2011) indicated that organic manures are fairly good source of nutrients which boosted plants to uptake progressively beneficial elements, to increase the leaf nutrient status and eventually attain optimum growth and productivity.…”
Section: Inorganic Nutrient Contentsmentioning
confidence: 99%
“…In addition, spraying rocket plants with the twig extract at the three rates 1, 2 and 3% elicited gradual increases in the amounts of these photosynthetic pigments but these increases were comparably less than those of Moringa leaf extract. Corroborative data were obtained using different types of organic fertilizers as compost, vermincompost, animal manure and seaweeds (Amujoyegbe et al, 2007;Noori et al, 2010;Abdalla and El-Khoshiban, 2012). The present knowledge ascertained that Moringa (leaves, seeds, pods) contains appreciable amounts of specific plant pigments with demonstrated potent antioxidant properties such as the carotenoids (lutein, alphacarotene, beta-carotene and xanthin) and chlorophyll (Owusu, 2008).…”
Section: Gas Exchange Measurements Photosynthetic Pigments Carbohydmentioning
confidence: 99%
“…Afaf A. Nessem # and Rania A. El-shenody Botany Department, Faculty of Science, Tanta University, Tanta, Egypt. AFAF A. NESSEM AND RANIA A. EL-SHENODY positively reduce the levels of lead and cadmium in plants as well as conductivity of soil but raised its pH (Abdalla & El-Khoshiban, 2012).…”
Section: Mitigation Of Lead Stress In Triticum Aestivum By Seed Primimentioning
confidence: 99%
“…Moringa leaves are potential source of vitamin A and C, iron, calcium, riboflavin, b-carotene, phenolics (Nambiar et al, 2005) and powerful natural antioxidants (Njoku and Adikwu, 1997). Now-a-days, moringa plant has attained enormous attention because of having cytokinin, antioxidants, macro and micro nutrients in its leaves (Abdalla and El-Khoshiban, 2012;Abdalla, 2013). Moringa has proved to be a potential source for research as scientists have moved their focus to this "Miracle tree".…”
Section: Introductionmentioning
confidence: 99%